2021
DOI: 10.1097/adt.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Correlates of Substance Use in a Sample of Egyptian Female University Students

Abstract: Objectives: The aim was to find out the prevalence of psychoactive substance use among female students in Ain Shams University, Cairo, and to investigate associations between substance use and some selected sociodemographic factors. Materials and Methods: A total of 600 female students in their final year of college was recruited from six faculties of Ain Shams University; 3 practical faculties (medicine, dentistry, pharmacy) and 3 theoretical faculties (commerce, arts, law), 100 students from each. They com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Regarding the research on substance use during university study in Egypt, few of these studies were performed on male [19] students while others on female students [20] but the majority were conducted on both genders [7,13,21]. Only a few of the previous studies demonstrated the pattern and risk factors of substance use in university students while the majority just reported if there was substance intake or not.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the research on substance use during university study in Egypt, few of these studies were performed on male [19] students while others on female students [20] but the majority were conducted on both genders [7,13,21]. Only a few of the previous studies demonstrated the pattern and risk factors of substance use in university students while the majority just reported if there was substance intake or not.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a similar percentage of the prevalence of illicit substance abuse (9.8%) was detected in medical and nonmedical female Cairo university students (El-Ghonemy et al 2021). Furthermore, more than half of the students agreed that use of PESs is another form of substance abuse which could be a starting point for health education in Egypt.…”
Section: Attitude and Use Of Pess By The Medical Studentsmentioning
confidence: 68%